Perilaku Switching pada Perbankan dalam Kajian Filsafat Ilmu - Aidha Trisanty; Mugi Harsono; Istinganah Eni Maryanti (ITB AAS INDONESIA, 2023)
This article describes the theoretical framework of the construct of switching behavior through a philosophy of science approach. This theoretical framework describes switching behavior in ontology, epistemology, axiology, antecedents, and consequences. This article is a literature study using a linear reference source search accessed through journals, books, articles, and information on websites from 1987 to 2021. Access references through the Directory of Open Access Journals (DOAJ), Scopus, ResearchGate, Google Scholar, ScienceDirect, and ProQuest. Previous research on switching behavior is divided into two aspects there are consumer behavior and consumer psychology, but the previous research and literature have focused more on aspects of consumer psychology. The literature on switching behavior is still segmented into switching behavior between banks or between Financial Technology. This article describes switching behavior from banking service customers to Financial Technology with the millennial lifestyle variable as a moderating variable.